THE INFLUENCE OF PROFESSIONAL SKEPTICISM, TASK COMPLEXITY, AND UNDERSTANDING OF THE CODE OF ETHICS ON ACCOUNTANTS' ABILITY TO DETECT FINANCIAL STATEMENT FRAUD (A STUDY AT ACCOUNTING SERVICE OFFICES IN INDONESIA) - Vicki Syarif; Febrian Kawarto (Publikasi Inspirasi Indonesia, 2024)
Financial statements are documents that present the financial position resulting from the accounting process over a specific period. These documents serve as a means of communication for stakeholders with relevant interests. This research aims to examine and analyze the influence of professional skepticism, task complexity, and understanding of ethical codes on accountants' ability to detect financial statement fraud. There are 4 variables in this study: professional skepticism, task complexity, and understanding of ethical codes as independent variables, and financial statement fraud as the dependent variable. The population in this study consists of accountants working in public accounting firms. The sample was selected using purposive sampling method based on several criteria supporting the research. The results of this study indicate that Professional Skepticism has a positive impact on Financial Statement Fraud, Task Complexity has a negative impact on Financial Statement Fraud, and Understanding of the Code of Ethics has a positive impact on Financial Statement Fraud.